2′-O-Galloylhyperin Isolated From Pyrola incarnata Fisch. Attenuates LPS-Induced Inflammatory Response by Activation of SIRT1/Nrf2 and Inhibition of the NF-κB Pathways in Vitro and Vivo - Wang, Peng; Gao, Chang; Guo, Na; Zhang, Sun-Dong; Wang, Wei; Yao, Li-Ping; Zhang, Jing; Efferth, Thomas; Fu, Yu-Jie (Frontiers in Pharmacology, 2018)
2′-O-galloylhyperin (2′-O-GH), a major compound of P. incarnata Fisch, possesses a variety of biological and pharmacological activities, including anti-oxidative and anti-inflammatory activities. Nevertheless, the underlying molecular mechanisms of 2′-O-GH in microbial infection and sepsis are not clear. In this study, we investigated the anti-inflammatory effects of 2′-O-GH. We found that 2′-O-GH signiﬁcantly reduced the production of tumor necrosis factor α (TNF-α), interleukin 6 (IL-6) and nitric oxide (NO), suppressed the expression levels of inducible nitric oxide synthase (iNOS), blocked the translocation of nuclear factor-κB (NF-κB) from the cytosol to nucleus, and decreased the MAPK activation in LPS-activated RAW 264.7 cells. 2′-O-GH also enhanced the nuclear translocation of nuclear transcription factor erythroid 2-related factor (Nrf2) and up-regulated the expression of heme oxygenase-1 (HO-1) and silent mating type information regulation 2 homolog 1 (SIRT1). In addition, the administration of 2′-O-GH attenuated the TNF-α and IL-6 production in the serum, infiltration of inflammatory cells, liver tissue damage and the mortality rate of lipopolysaccharides (LPS)-challenged mice. Moreover, 2′-O-GH significantly upregulated Nrf2 and SIRT1 expression and inhibited the inflammatory responses in the liver of septic mice. The collective data indicate that 2′-O-GH could potentially be a novel functional food candidate in the treatment of sepsis.